Process parameter, mineralogy, and wettability influence for CO2 adsorption on Terengganu shale samples and their interrogation on improved oil recovery - Abdulkareem, D.F. (European Association of Geoscientists and Engineers, EAGE, 2021)
In this study, adsorption of CO2 on Terengganu shale core samples will be discussed. The working parameters effect on adsorption capacity such as temperature and pressure are studied. A number of analytical analyses such total organic carbon (TOC), X-ray diffraction (XRD), Fourier Transform Infra-red Spectroscopy (FTIR), field Emission Scanning Electron Microscopy (FESEM), surface area and porosity analyzer (Brunauer, Emmett and Teller (B.E.T.)) are investigated. The volumetric adsorption technique is utilized to conduct adsorption measurements at up to 150 bar pressure and 30, 45, and 70oC temperatures to stimulate reservoir conditions. The adsorption and measurements are described in term of equilibrium isotherm models such as Langmuir, Freundlich, Toth, and Sips to demonstrate the adsorption process in term of physical/chemical, homogeneous/heterogeneous, monolayer/multilayer, and pore filling phenomenon. The kinetic measurement of shale sample is analyzed based on Pseudo First Order and Pseudo Second Order. The results showed that shale characteristics in term of minerology and porosity can plays a vital role in CO2 adsorption capacity. The total organic carbon (T.O.C) for the collected sample shows a range of 2.0 â 3.0 weight percent, which provides an indication of organic matter present. The mineralogy of the Terengganu core shale sample shows the evidence of clay minerals present up to 45 in the rock geometry, which can be an important factor to provide a potential to adsorb CO2 gas .Furthermore, the FESEM results provide a solid evidence of clay mineral present on surface. The average pore size of shale samples are in the range of 13.5 â 14.1 Nm which represents the shale samples as mesoporous. Based on the isotherm plots, result shows the type II adsorption isotherm according to the Brunauer, Deming, and Teller classification. This indicates the occurrence of micro-pores filling. Pressure and temperature parameter plays a major role in CO2 adsorption capacity in shale rock. Increasing the pressure with low temperature can increase the amount of CO2 adsorption in rock. Moreover, increasing pressure and temperature may result in less CO2 adsorption, which can supports physical adsorption as the dominant process. The best fitted isotherm models with the experimental results are Langmuir, Freundlich and Toth, which supports both mono- and multilayer with heterogeneous coverage. The k2 (diffusion) rate constant illustrates higher values compared to k1 (chemisorption) for all Terengganu shale sample with different temperature. Higher rate of constant in this work is shown by the diffusion process. A diffusion phenomenon is more dominant than chemisorption during CO2 adsorption. The findings of this study could help provide detail information about the influence parameters pressure, temperature, and mineralogy that increase the potential of CO2 adsorption and indirectly contribute to enhancing oil recovery (EGR). Â© EAGE Asia Pacific Virtual Geoscience Week 2021. All rights reserved.